ADOLESCENT BEHAVIOR IN UNWANTED PREGNANCY PREVENTION - Panjaitan, Arip Ambulan (INTERNATIONAL JOURNAL OF RESEARCH IN LAW, ECONOMIC AND SOCIAL SCIENCES, 2019)
Introduction: Adolescent are at high risk of unwanted pragnency, including abortion, STIs, HIV/AIDS. Risky sexual behavior is one of the entrance transmissions of unwanted pregnancy. Such behavior can be influenced by various factors, beyond and within the individual factors. Teens need the support and motivation in deciding not to do risky sexual behavior. The purpose of this study was to investigate the determinants of adolescent behavior in the prevention of unwanted pregnancy.Methods: This research used cross-sectional design. The populations were students of senior high school in District Sintang. The were 123 respondents chosen by cluster sampling technique for this study. All data were collected using questionnaires and then analysed using bivariate (chi square) and multivariate analysis (logistic regression).Results: The results showed that the majority of respondents did not have good knowledge about the prevention of unwanted pregnancy. Related variable is the level of parental education (p=0.001), the support of parents/guardians (p=0.009), support teachers (p=0.005), peer support (p=0.039), residency (p=0.009), a pastime activity (p=0.000), knowledge of adolescents about reproductive health (p=0.016), perception ability of adolescents (p=0.006) and attitude of adolescents (p=0.049). Adolescent self-perception abilities are variables that most influence on the behavior of adolescents in the prevention of unwanted pregnancy.Conclusions: Efforts to improve reproductive health programs should be early and adolescent have responsibilities as well as healthy behaviors.